A Comparison of the Bone Seeking Properties of Short-Chained 99mTc-Sn-Polyphosphates - Schümichen, C.; Nakken, K. F. (Nuklearmedizin - NuclearMedicine, 1974)
The bone seeking properties of short-chained 99mTc-Sn-polyphosphates were studied in rats. The average chain lengths of the polyphosphates ranged from n = 2 to n = 6. 85Sr was used as a standard for comparison. There was a trend of less bone uptake as well as higher soft tissue and blood concentration with increasing chain length. This and the results of clinical studies indicate that of all 99mTc-Sn-polyphosphates investigated the pyrophosphate complex is the most suitable one for skeletal imaging.